A utilização do laboratório de matemática para o ensino e aprendizagem de trigonometria no 2º ano do Ensino médio - Costa, Camila Lima da (2016)
This thesis presents an approach to the math lab in the school context, with a view to use of manipulatives in trigonometry. The goal is to guide teachers of Alagoas State Education Network in preparing lessons using the math lab, in order to enrich the teaching trigonometry. Initially, it took a historical analysis about the contents to be addressed. After the bibliographical analysis, a survey with teachers of state schools that are also students of PROFMAT / UFAL was held, addressing possible difficulties in using mathematics laboratory. Then it created a didactic sequence using math lab materials being applied in the 2nd year high school classes of the State School Odete Bonfim, Maribondo - AL. The aim of this work suggest to teachers and future teachers of mathematics, a material that can be used in the classroom to assist Trigonometry teaching, thus seeking improvements in teaching and learning by inserting the math lab at school.